RAPID DIAGNOSIS AND EXCELLENT TREATMENT IN EXTREMELY RARE AND LIFE-THREATENING THYROID STORM - Soekamto, Candra Christian; Kusumajaya, Bastianto; Budiharto, Tanto; Budiharto, Tanto; Wendra, Sadya; Hartono, Widawaty; Libriansyah; Allizaputri, Alfadea Irbah (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Thyroid storm is a life-threatening condition that requires rapid diagnosis, and emergent treatment and has extremely high mortality. Rapid diagnosis of this disease can be made using Burch and Wartofsky Criteria, supported by other examinations. Aggressive treatments for thyroid storm must be done as soon as possible, delayed treatment can increase the mortality rate to 90%. In Indonesia, treatment is based on the formula “T-424.1.666.6.8.24.6" which was developed by an expert Endocrinologist in Surabaya, Askandar Tjokroprawiro. We present two patients with thyroid storm, both of whom came in with full-blown symptoms of thyroid storm. However, the time onset of diagnosis and initial treatment since the first symptoms appeared was different. The first patient was diagnosed and treated earlier, but the second one was not. This case series was made to highlight that with rapid diagnosis and early, excellent treatment, thyroid storm can be fully treated.